Stable Isotopes and Mineralogy of Ordovician Clays, Southern Ontario, Canada in a Proposed Deep Geological Repository - Chauvin, Skylar (Université d'Ottawa / University of Ottawa, 2020)
The mineralogy, thermogravimetric behaviour, and δ2H and δ18O of <2μm size-fractions of Ordovician shales were analyzed from three different locations near Kincardine, Ontario. This location is the proposed site for a Deep Geologic Repository (DGR) for Low & Intermediate Level Waste. Based on powder X-ray diffraction (pXRD), the <2μm size-fraction of each unit was dominated by illite, with smaller amounts of kaolinite, and still smaller quantities of chlorite. Thermogravimetric analysis (TGA) undertaken in vacuo revealed multi-step weight loss patterns for these clay assemblages. Weight changes at the lowest temperatures were consistent with exchangeable cation-sensitive dehydration of surface-bound water. Stepped weight losses at higher temperatures were consistent with dehydroxylation patterns of illite, kaolinite and chlorite, as determined for standards from the Clay Mineral Society Source Clay Repository. These data guided removal of clay-bound surface water prior to extraction of hydroxyl group water when analyzing the oxygen and hydrogen isotope compositions of these low water-content shales. Clays in these Ordovician shales presumably formed during weathering of the east-coast Appalachian highlands of proto-North America. The δ2H and δ18O of the <2μm separates, however, do not plot on the clay weathering lines known for their major phases. This discrepancy is interpreted to indicate isotopic exchange (mostly of hydrogen) at temperatures typical of maximum burial at the DGR site (~90°C). The possibility of hydrogen isotope exchange between clay minerals and porewater in low water-content rocks has potential implications for preservation of original porewater isotopic compositions. This possibility should be tested in future work.
Keywords: Ordovician; Clay; DGR; Isotope; Hydrogen; Oxygen; NWMO; Mineralogy; TGA; XRD; Ontario